Similes analysis in Thai literature: A case study of "The happiness of Kati" in the English version - Hayeesa-i, Tasneem; Maisarah, Ira (Journal of Applied Studies in Language, 2023)
As our curiosity has led us to wonder why Thai children's literature with a simple plot, like Jane Vejjajiva's The Happiness of Kati, could actually captivate readers all over the world. By analysing the figurative language in the book, with an emphasis on similes as the scope, we would then try to demonstrate the hypothesis that the writer's story and her writing style have a significant relationship. According to the study's objectives, a list of all the similes used in the novel would be included in the study's findings, along with a list of the most frequently used similes based on the meaning analysis classification and the precise meanings behind them. These sought to establish the connection between the story and the author's writing style. Analysing descriptive data was used in the research. The process of gathering the data implies locating the similes that frequently appear in phrases and sentences and using the conjunctions "like" or "as." Both Richard's (1936) and Fromilhague's (1995) theories—simile analysis and simile meaning analysis—were applied in data analysis. The examined data were reviewed in order to determine the relationship between the story and the writer's writing style. The study found that there are 78 similes in the novel. 63 explicit and 25 implicit similes, or 68% and 32%, respectively, were discovered through meaning analysis. The author's writing style in her novel greatly enhances the plot that she develops in a variety of ways.